PRINCIPIO DE ECOMOMIA PROCESAL: LA CONCILIACION EXTRAJUDICIAL PREVIA A LA DEMANDA DE ALIMENTOS - Pilco Pilco, Liz Maria (2020)
I have carried out the work taking into account the judicial regulatory framework that are typical of the food demand processes, and whose request is to obtain through a firm judicial sentence, in the shortest possible time, it can be determined, the payment to cover the basic needs of the defendant's minor children. It is also necessary to mention that a judicial process, in our judicial system, is inefficient, and with the justification of the heavy procedural burden, it lasts months and sometimes years, so, in this case, the demands for food have to be applied, In the first place, before filing a lawsuit, the parties must seek to reconcile, so that the children of the couple in Litis, can reach a conciliatory agreement, for the sake that the children do not continue to be abandoned. If an agreement is not reached between the parties, a demand for food would have to be filed, and in this case, in order for it to be a process that is agile and is resolved in the shortest time, they must be incorporated as principles that seek that efficiency , that through the benefits generated in terms of time and economy, the Principle of Procedural Economy is taken into account; seeks to make less effort, time, savings; complying with the fundamentals of due process; and as a corollary of this action, the time would be significantly reduced and the burdensome procedural burden would decrease. This management, in order to speed up the process, is carried out while respecting fundamental principles that these types of judicial processes require, such as respect for legality and due procedure, which will allow them to be resolved in the shortest possible time, without violating any right during the procedural acts, Through this research work, a structure has been designed through which it will seek to explain and support the proposal In order to expedite, in terms of time, the demands for food, in the first place it is proposed that before the parties initiate or file a demand for food, it is proposed to try to reach a conciliation, to determine by mutual agreement the minimum amount necessary to cover basic needs and other conditions that allow reaching agreements that benefit the children more than anyone else, who are not to blame for their parents' problems, who do not have to have a good diet, which is directly related to having problems with their studies, in addition to not having the necessary supplies to fulfill their tasks, having adequate clothing and when necessary they can cover health expenses. As we can see, it is a problem, where if they are not cared for on time, the ones who suffer are the sons and daughters, as they do not have the food allowance that does not allow them to have a basic diet, that they cannot attend classes, and that being sick do not have money to cover their health problems. It is a situation, as we pointed out previously, where the most unprotected are children and where the Peruvian State must pay attention, because in the end, it is its function to protect them, but reality shows us that the Peruvian State, through Its different ministries and public entities related to protecting children do not fulfill their functions of protecting them, further aggravated by the abandonment of the father, sometimes both, which contributes in some way to increasing school dropout, increasing anemia child in the country. This shows that both the judicial system and the public entities of the State destined to protect the children of the country is deficient and inopportune.